(untitled) (Journal of Parents and Teachers, 2025)
María Menéndez Ponte tells the story of Diego, her son, who was born prematurely with serious medical complications. The author explains that his first two months of life were the hardest. He was diagnosed with brain damage and hypotonia. However, thanks to rehabilitation, exercises and therapies, Diego improved and learned to strengthen his body although the road was difficult and still is.